Yurchenko I.V., Yasynskyy V.K. The existence of Lyapunov-Krasovskii functionals for stochastic differential-functional Ito-Skorokhod equations under the condition of the solutions stability on probability with finite aftereffect // Cybernetics and Systems Analysis.– 2018.– Vol.54, Iss.6.– P.957-970. - Yasynskyy, Volodymyr Kyryllovych; Yurchenko, Igor Valeryjovych (Springer Science+Business Media, LLC, 2018)
In the paper, it is established that Lyapunov–Krasovskii functionals with definite properties exist for dynamic systems of random structure with finite prehistory and with the property of one or another probability stability.
In the paper, it is established that Lyapunov–Krasovskii functionals with definite properties exist for dynamic systems of random structure with finite prehistory and with the property of one or another probability stability.
Keywords: systems of random structure, aftereffect, stability, Lyapunov–Krasovskii functionals